Intergenerational genetic programming mechanism and sex differences of the adrenal corticosterone synthesis dysfunction in offspring induced by prenatal ethanol exposure. (15th October 2021) - Cao, Jiangang; Chen, Yawen; Xia, Xuan; Qu, Hui; Ao, Ying; Wang, Hui
Highlights: Low expression of P450scc mediates the inhibition of steroid hormone synthesis in PEE fetal adrenal glands. GR/SF1/HDAC1-regulated epigenetic changes mediate intrauterine inhibition of P450scc. PEE adult offspring shows sex differences in adrenal steroid hormone synthesis function injury. The H3K9ac of P450scc mediates the intergenerational inheritance of adrenal steroid hormone synthesis function abnormity in PEE adult offspring. Abstract: We previously found that prenatal ethanol exposure (PEE) induced adrenal dysplasia in offspring, which was related to intrauterine maternal glucocorticoid overexposure. This study investigated the intergenerational genetic effect and sex differences of PEE-induced changes in the synthetic function of adrenal corticosterone in offspring, and to clarify the intrauterine origin programming mechanism. Wistar pregnant rats were gavaged with ethanol (4 g/kg bw/d) from gestation day (GD) 9–20, and F1 generation was born naturally. The F1 generation female rats in the PEE group were mated with normal male rats to produce F2 generation. Serum and adrenal glands of fetal rats and F1/F2 adult rats were collected at GD20 and postnatal week 28. PEE increased the serum corticosterone level, while diminishing the expression of adrenal steroid synthases of fetal rats. Moreover, PEE enhanced the mRNA expression of GR and HDAC1, but inhibited the mRNA expression of SF1 and reduced the H3K9ac level of P450scc in the fetal adrenal gland. In PEE adult offspring of F1 and F2 generation the serum corticosterone level, the H3K9ac level of P450scc and its expression were decreased in males but were increased in females. In NCI-H295R cells, cortisol reduced the production of endogenous cortisol, down-regulated SF1, and up-regulated HDAC1 expression by activating GR, and decreased H3K9ac level and expression of P450scc. In conclusion, PEE could induce adrenal dysplasia in offspring with sex differences and intergenerational genetic effects, and the adrenal insufficiency in male offspring was related to the induction of low functional genetic programming of P450scc by intrauterine high corticosterone through the GR/SF1/HDAC1 pathway.